1997
DOI: 10.1002/(sici)1097-0215(19970917)72:6<1095::aid-ijc26>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

In vitro pancreatic ductal cell carcinogenesis

Abstract: Our experiments were designed to identify initial biochemical and biological changes that occur during pancreatic carcinogenesis. TAKA‐1, an immortal hamster pancreatic ductal cell line, was treated in vitro for up to 11 weeks with the pancreatic carcinogen N‐nitorosobis(2‐oxopropyl)amine (BOP). These treated cells were designated TAKA‐1 + BOP. The growth of TAKA‐1 and TAKA‐1 + BOP cell lines was investigated in soft agar and in hamsters intradermally. The resulting tumor from TAKA‐1 + BOP was re‐cultured in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…These findings are in accord with reports that Ki-ras mutations are not essential for in vitro carcinogenesis of hamster pancreatic ductal cells by the pancreatic carcinogen N-nitrosobis-(2-oxopropyl)-amine (BOP; Ikematsu et al 1997) although BOP-induced pancreatic carcinomas in hamsters expressed activating point mutations in the Ki-ras gene (Kranen et al 1991). Similar to the BOP hamster model (Okita et al 1995), the pancreatic tumors induced transplacentally by ethanol and NNK in our study lacked p53 mutations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are in accord with reports that Ki-ras mutations are not essential for in vitro carcinogenesis of hamster pancreatic ductal cells by the pancreatic carcinogen N-nitrosobis-(2-oxopropyl)-amine (BOP; Ikematsu et al 1997) although BOP-induced pancreatic carcinomas in hamsters expressed activating point mutations in the Ki-ras gene (Kranen et al 1991). Similar to the BOP hamster model (Okita et al 1995), the pancreatic tumors induced transplacentally by ethanol and NNK in our study lacked p53 mutations.…”
Section: Discussionsupporting
confidence: 92%
“…Pancreatic ductal adenocarcinomas frequently demonstrate activating point mutations of the Ki-ras gene (Hruban et al 1993). The incidence of these mutations is lower in smokers who also drink than in smokers who do not (Malats et al 1997), and it has been shown that mutations of Ki-ras and p53 were not essential for transformation of pancreatic ductal cells in vitro (Ikematsu et al 1997). Moreover, it has been shown that over-expression of (AA)-metabolizing enzymes in pancreatic cancers is associated with highly aggressive clinical behavior (Tucker et al 1999), while mutations in the Ki-ras gene have been associated with prolonged survival and responsiveness to therapy (Malats et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Determination of AA release from pre-labeled cells Cells were seeded into six-well plates (1·10 5 8.0 g NaCl, 5.6 mM D-glucose in 1 l of water, pH 7.4) containing 0.1% bovine serum albumin (BSA), cells were incubated in 2 ml of HBSS with 0.1% BSA for 45 min followed by acute exposure to NNK or isoproterenol (1 nM/10 min). Addition of BSA to the medium allowed entrapment of the released fatty acids, inhibiting subsequent metabolism and reacylation.…”
Section: Measurement Of Cyclic Amp Levelsmentioning
confidence: 99%
“…However, pancreatic ductal adenocarcinomas induced in hamsters by NNK and ethanol did not express activating point mutations of ras [7]. Additionally, it has been shown that neither mutations of Ki-ras nor p53 were essential for the malignant transformation of pancreatic ductal epithelia in vitro [8].…”
Section: Introductionmentioning
confidence: 99%
“…Histological findings point to the development of malignant glands in the center of islets, the exclusive position of β-cells in hamsters; 6) Malignant transformation of freshly isolated hamster pancreatic islets by BOP in vitro [33]. Although the treatment of cultured hamster pancreatic ductal cells also led to the formation of ductal adenocarcinomas [34] these tumors, contrary to those derived from islet cells [33], did not show the mutation of the c-K- ras oncogene [35], the most common genetic abnormality in human pancreatic adenocarcinomas [36,37]. Additionally, only the cultured islets cells treated with BOP showed an inactivation of the p16 (INK4a) gene (homozygous deletion) [38], which is found in 90–100% of human pancreatic adenocarcinomas [39]; 7) BOP-treatment of freshly isolated islets containing β-cells, but not those which were depleted of β-cells, resulted in malignant transformation (unpublished); 8) Isolated human islets but not human ductal cells treated with BOP could be grown in serum-free, growth factor-free medium and showed a mutation of c-Ki- ras (unpublished).…”
Section: Reviewmentioning
confidence: 99%